1986
DOI: 10.1007/bf02555109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endogenous estrogen fluctuation on metabolism of 25-hydroxyvitamin D

Abstract: To test the hypothesis that estrogen modulates the metabolism of 25-hydroxyvitamin D (25(OH)D) to 1,25-dihydroxyvitamin D (1,25(OH)2D) and 24,25-dihydroxyvitamin D (24,25(OH)2D), we studied 20 normal premenopausal women at four consecutive weekly intervals during one menstrual cycle. Estrogen stimulation was semiquantitatively defined into baseline, low-grade, or medium-grade categories, based on endogenous estrone and estradiol concentrations. 1,25(OH)2D increased incrementally from baseline levels of 34 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 26 publications
3
32
0
1
Order By: Relevance
“…The pathogenesis of AIMSS and why it may respond to vitamin D is unclear. One hypothesis is that estrogen deficiency causes a reduction in the activity of 1-alphahydroxylase, the enzyme that catalyzes the hydroxylation of calcidiol (25(OH)D) to calcitriol (1-25(OH) 2 D) [37]. Moreover, AI therapy may increase the requirements of vitamin D through competition with hepatic CYP3A4 [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of AIMSS and why it may respond to vitamin D is unclear. One hypothesis is that estrogen deficiency causes a reduction in the activity of 1-alphahydroxylase, the enzyme that catalyzes the hydroxylation of calcidiol (25(OH)D) to calcitriol (1-25(OH) 2 D) [37]. Moreover, AI therapy may increase the requirements of vitamin D through competition with hepatic CYP3A4 [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in total 1,25(OH) 2 D (13, 14) has been reported, though others found no such effect (15). Most, but not all (14), studies report an increase in the concentration of DBP (2,13). Two studies report no change in the free 1,25(OH) 2 D index during oral estrogen intake (8,13), but the actual free concentration was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in total 1,25(OH) 2 D has been found (8,13,14), but also no increase (15). Only two studies investigated the free index and found it to remain constant (8,13).…”
Section: Introductionmentioning
confidence: 99%
“…the VDR and vitamin D binding protein, which is the main vitamin D metabolite carrier in the circulation. 22,40,41 Estrogen also appears to downregulate vitamin D 24-hydroxylase, the main catabolic enzyme in the vitamin D pathway. 22,42 Together, these actions may result in elevated circulating vitamin D metabolites, although the clinical significance of this effect remains unknown.…”
Section: Discussionmentioning
confidence: 99%